Akkaraman koçların serum testosteron düzeylerinde ve spermatogenesisindeki mevsime bağlı değişikliklerin araştırılması. I. Spermatolojik özelliklerle testosteron miktarı arasındaki ilişki (Investigation of Seasonal Changes in Serum Testosterone Levels and Spermatogenesis in Akkaraman Rams. I. Correlation Between Spermatological Characteristics and Serum Testosterone Levels). - Türk, G; Demirci, E (My University, 2005)
This study was conducted to investigate the seasonal changes in serum testosterone levels and spermatological characteristics in Akkaraman rams. In this investigation, 120 Akkaraman rams, which were brought to the slaughterhouse for slaughtering and whose ages ranged between 14-18 months, were used. Semen was collected by an electroejaculator. Volume, motility, concentration and rate of abnormal spermatozoa were determined in collected semen. Blood samples were taken from jugular vein and centrifuged at 5000 rpm for 10 minfor serum extraction. The amount of testosterone was determined by coated tube RIA method using the serum stored at deepfreeze at -20°C. While the highest annual values of semen volume, sperm motility, sperm concentration and testosterone were determined as 1.11±0.03 ml, 84.66±1.01%, 3.21±0.07x109/ml and 6.35±0.16 ng/ml respectively in September. The lowest values of these parameters were determined as 0.56±0.03 ml, 63.32±0.99%, 2.03±0.06x109/ml, 2.69±0.08 ng/ml respectively, in February. Semen volume, sperm motility, sperm concentration and amount of testosterone reached their maximum levels in autumn and minimum levels in winter. Variations of these parameters among months, seasons were statistically significant (p<0.05). There were significant (p<0.01, p<0.05) correlations among semen volume, sperm motility, sperm concentration, amount of testosterone during four seasons. In conclusion, spermatological characteristics and amount of testosterone in Akkaraman rams were affected significantly by changing months and seasons and these features had a positive effect on fertility and showed the most improvement especially in autumn, the breeding season for rams.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Koç Spermatolojik Özellikler Testosteron Mevsim (Ram Spermatological Characteristics Testosterone Season)